Local Muscle Endurance and Strength Had Strong Relationship with CrossFit® Open 2020 in Amateur Athletes - Ramires Alsamir Tibana; Ivo Vieira de Sousa Neto; Nuno Manuel Frade de Sousa; Caroline Romeiro; Adriana Hanai; Hiury Brandão; Fábio Hech Dominski; Fabricio Azevedo Voltarelli (MDPI AG, 2021)
This study analyzed the relationship between anthropometric measures, cardiorespiratory capacity, strength, power, and local muscle endurance with performance in the CrossFit® Open 2020. For this, 17 volunteers (6 women) (29.0 ± 7.2 years) completed, on separate weeks, tests for body composition (dual-energy X-ray absorptiometry), maximal oxygen consumption (2 km row test), muscle strength (one repetition maximum (1 RM) back and front squat, isometric peak torque), muscle power (1 RM snatch and clean and jerk) and muscle endurance (Tibana test), which were compared with performance during the CrossFit® Open 2020. Specific tests of localized muscular endurance and muscle strength had the strongest relationship with performance in the CrossFit® Open 2020. On the other hand, the percentage of fat and cardiorespiratory capacity were not significantly correlated with CrossFit® Open 2020 workout performance. Coaches and practitioners should therefore utilize these findings to assess physical fitness and organize the distribution of the training session based on less developed physical needs, in order to ensure an appropriate physiological adaptation for a given competition.